THE EFFECT OF TURMERIC EXTRACT (CURCUMA LONGA) ADMINISTRATION IN KIDNEY HISTOPATHOLOGY FEATURES OF SPRAGUE DAWLEY RAT INDUCED BY 7,12-DIMETHYLBENZ(A)ANTHRACENE (DMBA) (Indonesian Urological Association, 2022)
Objective: The purpose of this study was to understand the effect of turmeric extract (Curcuma longa) on the histopathology features of male Sprague-Dawley rat’s kidney induced with 7,12-Dimethylbenz(a)anthracene (DMBA). Material & Methods: This is an experimental design with post-test only control group design with 6 experimental groups and 30 samples. A comparison model was made by comparing the first group (K1) received no DMBA and the second group (K2) received DMBA alone. Four groups (K3, K4, K5, K6) received DMBA and different dosages of turmeric extract. The exposure was given for 14 days and histopathology features of the samples were assessed using the Gibson-Corley scoring system for Interstitial Tissue Damage. The data obtained was analyzed using One-sample Kolmogorov-Smirnov normality test and then analyzed with the Dunnett t-test. Results: The interstitial tissue damage in the negative control group (K1) and positive control group (K2/DMBA) was found to have a significant difference (p 0.000). There was no significant difference between DMBA only (K2) group and the group with turmeric administration groups (K3, K4, K5, K6) (P<0.05). Conclusion: DMBA can alter kidney histopathology features of male Sprague-Dawley rats. Administering turmeric (Curcuma longa) orally did not cause a change in kidney histopathology features of male Sprague-Dawley rats induced by DMBA.